2020
DOI: 10.3389/feart.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the Power of the Mann-Kendall Test for Detecting Monotonic Trends in Hydrometeorological Time Series

Abstract: The Mann-Kendall (MK) statistical test has been widely applied in the trend detection of the hydrometeorological time series. Previous studies have mainly focused on the null hypothesis of "no trend" or the "Type I Error." However, few studies address the capability of the MK test to successfully recognize the trends. In some cases, especially when the trend test is jointly applied with hydropower station design, flood risk assessment, and water quality evaluation, the "Type II error" is equally important and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
126
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(130 citation statements)
references
References 63 publications
1
126
0
3
Order By: Relevance
“…These results are in perfect agreement with the findings of Yue et al [15], who analyzed the MK test power from generation performed with GEV parent distribution, with different values of the trend, coefficient of variation, and sample size. They are also consistent with the results shown by Wang et al [16] and extend the range of climatic variability explored by Totaro et al [14].…”
Section: Power Of Aic ∆ and Mk Tests For Different Values Of ε And L-cvsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in perfect agreement with the findings of Yue et al [15], who analyzed the MK test power from generation performed with GEV parent distribution, with different values of the trend, coefficient of variation, and sample size. They are also consistent with the results shown by Wang et al [16] and extend the range of climatic variability explored by Totaro et al [14].…”
Section: Power Of Aic ∆ and Mk Tests For Different Values Of ε And L-cvsupporting
confidence: 93%
“…They followed the approach proposed by Yue et al [15] that produced a numerical evaluation of the MK test power for Generalized Extreme Value (GEV) distributed samples. Wang et al [16] provided a practical relationship for a proper power assessment of specific time series.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found that the M-K test results of pre-whitening processed sequences were not accurate because of the loss of important information [85]. It is also suggested that the M-K test results can be improved by improving the significance test level and increasing the time series length of samples [64]. In the current study, the variation trend of relative humidity series was obvious, the sample size was large (1959-2017), and the confidence level of 95% was adopted.…”
Section: The Application Of Mann-kendall Trend Test Methodsmentioning
confidence: 99%
“…This study found that the autocorrelation of the time series of hydrological and meteorological elements had an impact on the M-K test results. Therefore, the autocorrelation of the relative humidity time series was tested before the M-K test, and the influence of significant correlation was eliminated by the means of variance correction [64,65].…”
Section: Detection Of Mann-kendall Mutationmentioning
confidence: 99%